Alice in Borderland. Volume 5 - Aso, Haro, 1980-; Werry, John (Translator) (VIZ Media, LLC, 2023)
"Eighteen-year-old Ryohei Arisu is sick of his life. School sucks, his love life is a joke, and his future weighs on him like impending doom. As he struggles to exist in a world that can't be bothered with him, Ryohei feels like everything would be better if he were anywhere else. When a strange fireworks show transports him and his friends to a parallel world, Ryohei thinks all his wishes have come true. But this new world isn't an empty paradise, it's a vicious game. And the only way to survive is to play. Arisu and his companions have managed to defeat the Dealers, but the battle isn't over yet. Now they must take on the Face Cards--12 players who have the dubious honor of being Borderland "royalty." Arisu hopes they are close to going home, but the games the Face Cards play might be worse than any of the cruelties the Dealers came up with."--